Inovasi Metaverse Dalam Transformasi Pelayanan Publik Di Kota Metropolitan Makassar - Muhammad Ramli (LPPM STIA Lancang Kuning Dumai, 2026)
Makassar City as a metropolitan city with the vision of becoming a world-class city, the concept of the Metaverse will be implemented in its government. This idea is considered appropriate to prepare for and respond to future technological advancements. This metaverse-based service is planned to operate virtually with 3D technology, enabling citizens to access public services in a more interactive manner. With the introduction of metaverse innovation, it is hoped that problems previously faced by the public can be resolved. This research delves deeper into the Metaverse Innovation in the Transformation of Public Services in Metropolitan Makassar. The study seeks to explore, analyze, and discover how the role of metaverse innovation contributes to the transformation of public services in major cities, especially Makassar as a metropolitan city. Naturally, handling public services has become increasingly dynamic, therefore requiring metaverse innovation through innovative, transformative, and credible methods, resulting in faster and more accessible public services to meet the needs of society. This research uses a qualitative method, with descriptive analysis focused on the main issues of the study. The research location is the city of Makassar. The findings show that, in reality, these innovations have made public service management in Makassar increasingly dynamic, as the issues faced are quite diverse. The Makassar City Government has adopted various innovations to facilitate public services in addressing the ever more complex needs of society, making use of digital technology to enhance the efficiency and transparency of public services. They have launched mobile applications and official websites that allow the public to access information, submit applications, and track service processes online. For example, the